Standardization and Validation of Non-invasive Monitoring of End Tidal Carbon Dioxide in Neonates via Nasal Cannula: An Observational Study - Varun R Nayak; Tisha Ann Skariah; Leslie Lewis (Mashhad University of Medical Sciences, 2019)
Background: Carbon dioxide (CO2) is a by-product of cellular metabolism, which could be considered as a reflection of metabolism, circulation, and ventilation. Arterial blood gas analysis (ABG) is the gold standard of monitoring for CO2. However, is an expensive method leading to blood loss and iatrogenic anemia. In addition, each sample is only a snapshot view of the sampling moment. End-tidal CO2 (ETCO2) measurement gives a non-invasive and continuous monitoring of exhaled CO2. Therefore, this study aimed to validate the non-invasive CO2 measurement performed by nasal cannula and evaluate the correlation with partial pressure of arterial CO2 (PaCO2 ) in neonates. Methods: This single-center observational study was conducted in the Neonatal Intensive Care Unit (NICU), Kasturba Hospital, Manipal, India. PaCO2 was reported on routine ABG within a 15-minute interval of ABG sampling. Moreover, partial pressure of end-tidal carbon dioxide (PetCO2) was noted at continuous 30-sec intervals (i.e., 30, 60, 90, ..., 180) up to 3 minutes. The values of PaCO2 and PetCO2 were found to be correlated with Pearson correlation and were shown by scattered plot. Regression analysis was used to get the prediction equation and the variance. Results: A total of 70 samples were taken in the initial phase to study the correlation between PaCO2 and measured PetCO2. Pearson correlation showed a moderate positive correlation (r= 0.589) between PetCO2 and measured PaCO2. Regression analysis demonstrated a variance of 33.8% between the measured PetCO2 and PaCO2, which was statistically significant (P